Synthesis of novel photosensitizer-silica nanoparticle hybrids for controlled (1O2) release in cancer photodynamic therapy - Borzecka, Wioleta (2019)
Cancer is one of the biggest health problem for humans. Until now, there is no efficient therapy for most cancers. An alternative method to conventional cancer treatments, including chemotherapy, radiotherapy and surgery, could be photodynamic therapy (PDT), which combines three components: a photoactive drug (photosensitizer, PS), a particular type of light and oxygen. In PDT, the severe side effects of chemotherapy or radiotherapy are minimized. However, as all clinical protocols, PDT still has some problems to solve. One of the difficulties in PDT is to find an ideal PS for the different tumors. Recently, nanoparticle-based delivery systems have been explored as efficient vehicles to deliver PSs in PDT. In particular, silica nanoparticles (SNPs) are attracting great attention in PDT due to their biocompatibility, large surface area, controllable size formation, hydrophilic surface and ability for surface functionalization. The possibility for tumor targeting through surface modification is a key to successful cancer treatment. As such, this dissertation describes the synthesis and characterization of novel photosensitizer-silica nanoparticle hybrids for controlled singlet oxygen (1O2) release in cancer PDT. The work is divided into three chapters in which novel nanoformulations are presented as third generation PSs for PDT. In the first part, S-glycoside porphyrins (Pors) were prepared and encapsulated into SNPs by Stöber method. In the next part, the same Pors were grafted on the surface of sphereshaped and rod-shaped mesoporous silica nanoparticles (MSNPs). Finally, NPs encapsulating phosphonate phthalocyanine (Pc) or covalently appended with Pc were prepared after slight modification of the reverse microemulsion method. These new nanomaterials show relatively homogeneous morphological characteristics, such as size and shape. The new nanocarriers are able to produce 1O2 after light irradiation and have been employed for in vitro studies with two human bladder cancer epithelial cell lines, HT-1376 and UM-UC-3. The results showed that the new nanoparticle-based systems could be successfully used as novel PSs in PDT of bladder cancer which is the fourth most commonly diagnosed cancer with the high rate of recurrence.